Large Deviations for Nonlinear Itô Type Stochastic Integrodifferential Equations - Suvinthra, M.; Balachandran, K. (Journal of Applied Nonlinear Dynamics, 2026)
In this work, we consider a nonlinear Itô type stochastic integrodifferential equation and study the Freidlin-Wentzell type large deviation principle for its solution processes. The weak convergence approach is employed to establish the Laplace principle which in turn is equivalent to the large deviation principle. The compactness criterion is verified by means of sequential compactness of solutions of the associated controlled equation. The weak convergence result is asserted via solutions of the controlled equation with stochastic perturbation. Finally, examples are included to illustrate the theory.